New techniques for quantification of biomarkers and metabolites by magnetic resonance imaging and spectroscopy - Christopher W. Jenkins (2019)
Since its early beginnings, almost ﬁve decades ago, MRI has revolutionised medical imaging, sustaining an active ﬁeld of research into new applications, and improved understanding of the underlying mechanisms. Its complexity and ﬂexibility, as a non-invasive imaging modality is simultaneously, an asset and a challenge. Quantitative imaging provides a particular challenge due to an increased sensitivity to experimental variations. The development of accurate and robust methods for quantitative magnetic resonance requires protocols to be carefully calibrated to produce consistent results. This necessitates the use of test objects with known, stable, conﬁgurable characteristics. This thesis is aimed at the development of these test objects, and their use within quantitative imaging, spectroscopy, and the development of new techniques.First, a set of magnetic resonance test objects were created, and their relaxation properties assessed. T1 and T2 are calculated using spin, and multi-spin echo sequences respectively. Several contrast and gelling agents were assessed, and the relaxivity estimated in each case. The protocol dependence of T1 estimation methods is examined using a phantom and in-vivo study. Saturation and inversion recovery estimations are compared to variable ﬂip angle methods, and the statistical distributions of T1 maps quantiﬁed. A series of calibrated phantom studies are conducted, assessing the analysis methods used for in-vivo magnetic resonance spectroscopy. The concentration of brain metabolites is varied within liquid and gel phantoms, and the ratio of GABA to NAA is calculated using a number of analysis tools, and in-house software.Finally, a magnetic resonance spectroscopy Hamiltonian simulator is implemented in Matlab. The simulator is utilised by collaborators in developing a quantum control framework. Optimal control is used to generate chemically selective RF pulses, and initial experimental implementations explored.The quantitative methods were found to exhibit both acquisition and analysis method dependencies. However, results were largely consistent within methodology, highlighting the need for consistency across sites to ensure valid comparison. The the-oretical development of novel RF pulses has been successful, but much work remains to approach experimental implementation.